Peran Data Analyst, Administration & Finance, dan Event Strategist Dalam Strategi Pemasaran Sosial Yayasan Setara Melalui Aktivasi Media Sosial, Sosialisasi Orang Tua, Rekrutmen Relawan, Main Event, dan Pendampingan Anak - Indah Zuzaharani; Yanuar Luqman (Interaksi Online, 2026)
Yayasan Setara faced the challenge of low brand awareness which hindered public participation and the effectiveness of its social programs. To address this, the program was designed utilizing a Social Marketing Theory approach combined with an Integrated Marketing Communication (IMC) strategy, encompassing public relations, direct marketing, and event marketing. All activities were focused on integrating community socialization, volunteer recruitment, and child advocacy programs to ensure consistent messaging that effectively influenced the audience’s social behavior. The campaign implementation involved the crucial roles of Data Analyst, Administration & Finance, and Event Strategist. The results of the implementation demonstrated significant achievements across both reach and engagement metrics. The primary impacts were an increase in information reach and the successful expansion of collaboration networks, proving a strengthened community commitment to child protection. Furthermore, the rise in public participation and awareness confirmed that the integrated communication strategy was well-received and processed effectively by the target audience in Semarang.